Trigonometry! #42

Geometry Level 3

Find the value of tan ( cos 1 ( 4 5 ) + tan 1 ( 2 3 ) ) \tan \left ( \cos^{-1} \left (\frac {4}{5} \right) + \tan ^{-1} \left (\frac {2}{3} \right) \right)

This problem is part of the set Trigonometry .

16 7 \frac {16}{7} 6 17 \frac {6}{17} 7 16 \frac {7}{16} None of these

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Murtaza Saifee
Jan 21, 2015

Let cos(x)=4/5 . Implies tan (x) = 3/4 (using Pythagoras Theorem)

Therefore cos^-1(4/5) = tan^-1(3/4)

Since tan^-1(a) + tan^-1(b) = tan^-1 [(a+b)/1-ab]

The equation left is: tan(tan^-1[{(3/4)+(2/3)}/{1- (3/4)(2/3)}]) = 17/6

Therefore the answer is : None of these

Omkar Kulkarni
Feb 14, 2015

Let cos x = ( 4 5 ) tan x = ( 3 4 ) \cos x =\left( \frac{4}{5}\right) \Rightarrow \tan x = \left(\frac{3}{4}\right)

cos 1 ( 4 5 ) = tan 1 ( 3 4 ) \therefore \cos^{-1}\left(\frac{4}{5}\right)=\tan^{-1}\left(\frac{3}{4}\right)

Hence, the expression becomes tan ( tan 1 ( 3 4 ) + tan 1 ( 2 3 ) ) = 3 4 + 2 3 1 ( 3 4 ) ( 2 3 ) = 17 6 \large{\tan\left(\tan^{-1}\left(\frac{3}{4}\right)+\tan^{-1}\left(\frac{2}{3}\right)\right) \\ = \frac{\frac{3}{4}+\frac{2}{3}}{1-\left(\frac{3}{4}\right)\left(\frac{2}{3}\right)} \\ = \boxed{\frac{17}{6}}}

@Omkar Kulkarni Why can't we take tan ( x ) = 3 4 \tan(x) = \dfrac{-3}{4} in the first step?

Ankit Kumar Jain - 4 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...